(untitled) (Studia Prawnicze / The Legal Studies, 2006)
Wolność religijna, zwana również wolnością sumienia i wyznania, wolnością sumienia i religii, wolnością myśli, sumienia i religii, czy wreszcie wolnością myśli, sumienia, religii lub przekonań, jest z pewnością rudymentarną wolnością człowieka. Nic więc dziwnego, że jest ona zapisywana i potwierdzana w aktach prawnych, w tym także rangi konstytucyjnej, znakomitej większości państw demokratycznych, stanowiąc istotny składnik wyznaczający status prawny jednostki. Wolność ta jest przy tym o tyle interesująca, iż ma ona dualny (podwójny, czy też może dwuczłonowy) charakter. Z jednej bowiem strony wolność ta obejmuje - i to przede wszystkim - tzw. wymiar indywidualny (jednostkowy), gwarantujący każdemu swobodę samookreślenia religijnego, a nawet szerzej światopoglądowego, z drugiej zaś tzw. wymiar, względnie aspekt, kolektywny (zbiorowy), który zapewnia wolność sumienia i wyznania wspólnot religijnych, czyli organizacji konfesyjnych przybierających postać kościołów bądź innych związków wyznaniowych. Stąd m.in. prawna regulacja wolności religijnej obejmuje dwojakiego rodzaju normy, po pierwsze te, których destynatariuszem jest pojedynczy człowiek, po drugie te, których adresatem są kościoły oraz inne związki wyznaniowe. The artical deals with freedom of religiuos (freedom of conscience and belif) which is currently recognized as a fundamental and most important human liberty. This freedom is closely linked, on the one hand, to the individual’s right to privacy and, on the other, to the religious neutrality of the State. A short time ago freedom of religious or freedom conscience and belif was defined by the use of many different words and phrases. Now it is undeniably considered as a guarantee of lack of interest on the part of the State for views, opinions, attitudes and judgment of its citizens or people in generał. As a result, in domestic regulations and particularly, in intemaltional norms, freedom of religious is meant to be interpreted in a very broad sense including the right of free choice of religion, the right to have and express different opinions including religious, non-religious and, finally anti-religious views. Hence, freedom of religious means a guarantee form individual to make free evaluations and choice of religion and any other opinions. Freedom of religious have two diferent and importent dimension. First, the individual dimension, which guarantee every human person freedom of conscience and belif, and the second, the collective dimension which guarantee every church ad ather religion organisations freedom means eąuality and autonomy and inde pendency. As a result the State is neutral what is tehe best guarantee for the human liberty and rights. For obvious reasons, the starting point of freedom of religious and neutral State is a democratic and plural political regime. Therefore the freedom of religious (freedom of belifs or freedom od philosophy of life or finally freedom of conscience and belif) is a real background of the growing cultural and religious plurality in the modem society.